Cathepsin S As an Inhibitor of Cardiovascular Inflammation and Calcification in Chronic Kidney Disease - Sena, Brena F.; Figueiredo, Jose Luiz; Aikawa, Elena (Frontiers in Cardiovascular Medicine, 2018)
Abstract Cardiovascular disease is responsible for the majority of deaths in the developed world. Particularly in patients with chronic kidney disease (CKD), the imbalance of calcium and phosphate may accelerate both vascular and valve inflammation and calcification. One in two patients with CKD are reported as dying from cardiovascular causes due to the resulting acceleration in the development of atherosclerosis plaques. In addition, CKD patients on hemodialysis are prone to aortic valve calcification and often need valve replacement before they undergo kidney transplantation. The lysosomal proteases, cathepsins, are composed of 11 cysteine members (cathepsin B, C, F, H, K, L, O, S, V, W, and Z), as well as serine proteases cathepsin A and G, which cleave peptide bonds with serine as the amino acid, and aspartyl proteases D and E, which use an activated water molecule bound to aspartate to break peptide substrate. Cysteine proteases, also known as thiol proteases, degrade protein via the deprotonation of a thiol and have been found to play a significant role in autoimmune disease, atherosclerosis, aortic valve calcification, cardiac repair, and cardiomyopathy, operating within extracellular spaces. This review focuses on evaluating recent findings in this field, highlighting how among cathepsins, the inhibition of cathepsin S in particular, could play a role in diminishing the effects of cardiovascular disease, particularly for patients with CKD. Keywords: cathepsin S, cardiovascular disease, chronic kidney disease, calcification, atherosclerosis, aortic valve